Xestia smithii - Pogue, Michael G. (Zenodo, 2006)
32. Xestia smithii (Snellen) Smith's Dart (Fig. 78, Map 49) Identification: Forewing length 14.0–19.0 mm. Xestia smithii looks like an unmarked X . normanianus . Forewing ground color is brown with some dark rufous overtones. Orbicular spot is a lighter shade than ground color, with an ovate shape, and edged with dark reddish brown. Reniform spot is ground color shaded with dark gray, especially in the ventral half. Antemedial and postmedial lines are a lighter shade than ground color and faint. Two small black spots are present at apex of subterminal line on costa. Hindwing dark gray, discal spot faint, and fringe cream. Flight period: Collected from late July to midOctober. Collected localities: North Carolina: Haywood Co., Purchase Knob, Purchase Knob cabin; Swain Co., Big Cove Road site b, Big Cove Road site c, Big Cove Road site p, Big Cove Road site w, 8.3 mi NE of GSMNP entrance on Kephart Prong Trail, 8.3 mi NW of GSMNP entrance on Kephart Prong Trail Mt. Buckley, Ravensford, upper Noland Divide Trail ca. Clingman's Dome. Tennessee: Blount Co., Tremont; Cocke Co., Cosby ATBI house, Cosby campground area, Foothills Parkway East, Foothills Parkway 2 nd overlook E ast; Sevier Co., Elkmont, 5 mi S Sugarlands Visitor Center Chimney's picnic area, 6 mi S Sugarlands Visitor Center. (34 specimens) MAP 49. Collecting localities of Xestia smithii. Elevation range: 1360–6560 ft. (415–1999 m) General distribution: This species is widespread across northern North America from Newfoundland to Alaska. In the eastern United States it occurs from Maine to Virginia and south along the Appalachians to North Carolina. In the west it is found in the Black Hills in western South Dakota and northeastern Wyoming, in the Rocky Mountains from Montana to New Mexico, southeastern Arizona, and from Washington to east central California (Lafontaine 1998). The collections from GSMNP are new records for the state of Tennessee. Larval hosts: Larvae feed on a variety of herbaceous and woody plants including strawberry ( Fragaria virginiana Duchesne), raspberry ( Rubus idaeus , Rosaceae), apple ( Malus sp., Rosaceae), alder ( Alnus sp., Betulaceae), common elderberry ( Sambucus nigra L. ssp. canadensis (L.) R. Bolli, Caprifoliaceae), and violets ( Viola sp., Violaceae) (Crumb 1956, McCabe 1991). Larvae have been known to cause serious damage to strawberry crops in Washington (Crumb 1956). : Published as part of Pogue, Michael G., 2006, The Noctuinae (Lepidoptera: Noctuidae) of Great Smoky Mountains National Park, U. S. A., pp. 1-95 in Zootaxa 1215 (1) on pages 65-66, DOI: 10.11646/zootaxa.1215.1.1, http://zenodo.org/record/5064764 : {"references": ["Lafontaine, J. D. (1998) Noctuoidea, Noctuidae (part): Noctuinae, Noctuini. In: Hodges, R. W., Davis, D. R., Dominick, T., Ferguson, D. C., Munroe, E. G., & Powell, J. A. (Eds.), The Moths of America North of Mexico, fasc. 25.3, Allen Press, Lawrence, Kansas. 348 pp.", "Crumb, S. E. (1956) The larvae of the Phalaenidae. United States Department of Agriculture, Technical Bulletin, 1135, 1 - 356.", "McCabe, T. L. (1991) Atlas of Adirondack caterpillars. New York State Museum Bulletin, 470, 1 - 114."]}